Is There a Double‐Negative Effect? Gender and Ethnic Wage Differentials in Italy. (15th April 2015) - Piazzalunga, Daniela
Abstract This paper investigates the gender and ethnic wage differentials for female migrants in Italy by applying the Oaxaca–Blinder decomposition, with and without Heckman correction, to account for self‐selection into the labour market. The gender wage gap is nearly 15 per cent, more than 60 per cent of which is unexplained by observable differences. The ethnic wage gap is much larger (39 per cent), but endowments explain 53 per cent of the gap. We also estimate the double‐negative effect of being both female and a migrant. A female migrant earns 42 per cent less than an Italian male; the unexplained component is estimated to be 53–65 per cent. Results are robust to different specifications.